Perilaku Manajemen Keuangan Mahasiswa Kelas Karyawan Di Cikarang - Setyawan, Wisnu; Wulandari, Siska (Universitas Pendidikan Indonesia, 2020)
AbstractFor some students, requires them to go to college while working to pay for their studies and living expenses. Financial management behavior has an important role in determining the success of their studies. This study aims to determine the financial management behavior of income-earning students, as well as the influence of financial literacy and financial attitudes on financial management behavior of employee class students in Cikarang.Â The method in this study is quantitative associative research, research that uses quantitative data, then processed through regression statistical testing in answering research hypotheses.Respondents were 100 faculty of economics students of the Pelita Bangsa University, consisting of 71 female students and 29 male students. The results showed that financial literacy and financial attitudes had a positive effect on financial management behavior of the employee class students in Cikarang, with a contribution of more than 61%.Keywords: employee class; financial attitudes; financial management behavior; financial literacy; student income-earning.AbstrakBagi sebagian mahasiswa mengharuskan mereka kuliah sambil bekerja guna membiayai studi dan kebutuhan hidup. Perilaku manajemen keuangan memiliki peran penting dalam menentukan keberhasilan studi mereka. Penelitian ini bertujuan untuk mengetahui perilaku manajemen keuangan mahasiswa berpenghasilan, serta pengaruhnya literasi keuangan dan sikap keuangan terhadap perilaku manajemen keuangan mahasiswa kelas karyawan di Cikarang. Metode dalam penelitian ini adalah penelitian asosiatif kuantitatif, penelitian yang menggunakan data kuantitatif, lalu diolah melalui pengujian statistik regresi dalam menjawab hipotesis penelitian. Responden adalah 100 mahasiswa kelas karyawan fakultas ekonomi Universitas Pelita Bangsa yang terdiri dari 71 mahasiswa perempuan dan 29 mahasiswa laki-laki. Hasil penelitian menunjukan bahwa literasi keuangan dan sikap keuangan berpengaruh positif terhadap perilaku manajemen keuangan mahasiswa kelas karyawan di cikarang, dengan kontribusi diterminasi lebih dari 61%.Kata kunci : kelas karyawan; literasi keuangan; mahasiswa berpenghasilan; perilaku manajemen keuangan; sikap keuangan